(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Heart rate variability (HRV) is an important indicator of the functional state of the body in younger school-aged children and reflects the balance between the sympathetic and parasympathetic branches of the autonomic nervous system. Studying HRV is particularly relevant in the context of increasing psycho-emotional and physical stress during the school period when the body’s adaptive mechanisms are actively developing and undergoing significant challenges. The method of HRV analysis combined with the active orthostatic test provides a comprehensive assessment of cardiovascular regulation, early detection of maladaptation, and preclinical changes. The use of this approach in screening studies allows for the identification of children at high risk of functional disorders, clarification of the features of autonomic regulation, and the development of personalized preventive measures. The high sensitivity of HRV indicators to stress factors, sleep quality, nutrition, and physical activity makes this method a valuable tool in pediatric practice. Early detection of deviations contributes to timely prevention of chronic diseases and the promotion of a healthy lifestyle in children.